Trend in Using Podcasts for Students Listening Skills: Systematic Literature Review - Sefriani Niode; Andi Nurwati; Hasan Ayuba; Mohd Rabe (Walidem Institute and Publishing, 2026)
Objective: This research aimed to investigate the growing implementation of podcasts to enhance students’ listening comprehension in higher education. Theoretical framework: Limited exposure to authentic spoken English and low student motivation remain persistent challenges in listening instruction, particularly in the digital learning era. Literature review: To address this issue, a Systematic Literature Review (SLR) was conducted using the PRISMA framework to synthesize current empirical evidence and map research trends from 2020 to 2024. Twenty-six relevant journal articles indexed in reputable academic databases were selected based on predetermined inclusion criteria. Methods: This study employed a Systematic Literature Review (SLR) to examine and synthesize previous studies. Results: The findings reveal a strong upward trend in podcast-based listening research, peaking in 2023, with quantitative designs dominating 53.8% of studies. The results confirm that podcasts significantly improve listening performance and motivate learners due to their flexible, on-demand nature. Three pedagogical strategies were consistently effective: extensive listening, metacognitive integration, and collaborative podcast production. Implications: The study concludes that podcast-mediated learning is a powerful and innovative approach, yet further structural development, such as local content adaptation and technological training, is needed to optimize its implementation in higher education. Novelty: The novelty of this study lies in its PRISMA-based systematic mapping (2020-2024) that synthesizes evidence on podcast effectiveness in listening comprehension while uniquely identifying three consistently effective pedagogical strategies and highlighting the need for local content adaptation and technological training in higher education.